Secondary battery and electric device
By using a combination of garnet-type compounds and silicon-based/carbon-based materials in the negative electrode sheet of lithium-ion batteries, the negative electrode active layer is formed, which solves the polarization and expansion problems during fast charging of lithium-ion batteries and improves the rapid battery life Charging and discharging performance, while ensuring safety performance, is suitable for silicon-containing and graphite-containing negative electrodes.
Patent Information
- Application Number
- CN202310880032.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-01-17
AI Technical Summary
When lithium-ion batteries are fast charging, due to the poor dynamic characteristics of the negative electrode material, it is easy to cause polarization and safety problems, which limits the fast charging performance of lithium-ion batteries, especially the rapid expansion of the negative electrode containing silicon is difficult to solve.
Introduce specific solid electrolytes, such as garnet-type compounds, and combine silicon-based and carbon-based materials to form an active negative electrode layer, reduce internal resistance and improve ionic conductivity. It is suitable for silicon-containing negative electrodes and traditional graphite negative electrodes, and improves the Fast charging performance.
It realizes good fast charging and discharge performance of lithium-ion batteries, maintains high safety performance, is suitable for high energy density batteries, and does not require large-scale changes in the negative electrode main material, which has good universality.
Smart Images

Figure BDA0004344738630000161 
Figure HDA0004344738640000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a secondary battery and an electrical device. Background Art
[0002] Lithium-ion batteries have been widely used and deeply researched and developed in consumer electronics and electric vehicles due to their high energy density and long cycle life. As people's pace of life accelerates, the demand for shortening charging time in the consumer electronics and electric vehicle industries continues to increase, thus placing higher requirements on the fast charging performance of lithium-ion batteries.
[0003] Traditional negative electrode active materials include carbon-based materials (such as graphite) and silicon-based materials, but the kinetic properties of both as negative electrode active materials are poor. The lithium insertion potential of the graphite negative electrode is below 0.2V. When the lithium-ion battery is rapidly charged, polarization occurs, which is very easy to cause lithium precipitation at the negative electrode, thereby deteriorating the cycle performance of the battery and even causing safety problems. When the silicon-containing negative electrode is rapidly charged in the lithium-ion battery, it will expand rapidly, thereby deteriorating the cycle and safety performance of the lithium-ion battery. Therefore, the negative electrode has become the main limiting factor for improving the fast charging characteristics of lithium-ion batteries. At present, the main means to optimize the fast charging performance of lithium-ion batteries include using fast-charging graphite negative electrode materials, adding additives to the electrolyte, optimizing the battery structure design to reduce internal resistance, and increase the current capacity. However, these methods all require large-scale changes in the main negative electrode materials, or the use of complex additives, or changes in the battery structure design, which are difficult to promote and apply. Summary of the invention
[0004] Based on this, the present invention provides a secondary battery and electrical device that does not require large-scale changes to the negative electrode main material and can reduce internal resistance and maintain good fast charging performance when used in high energy density batteries such as silicon-containing negative electrodes, while having good discharge performance and high safety performance.
[0005] The specific technical solutions are as follows:
[0006] In a first aspect of the present application, a secondary battery is provided, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet;
[0007] The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on the surface of the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material and a solid electrolyte, wherein the solid electrolyte includes a garnet-type compound, and the garnet-type compound includes Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.4 Ln3Z 1.4 Ta 0.6 O12 , Li 6.6 Ln3Z 1.6 Ta 0.4 O 12 , Li 6.75 Ln3Z 1.75 Ta 0.25 O 12 , Li 6.625 Ln3Z 1.625 Ta 0.375 O 12 、Li5La3M2O 12 and Li3Zr2Si2PO 12 One or more of; wherein M is selected from one or more of Zr, Ge, Mg and Al.
[0008] In one embodiment, the Dv50 particle size of the garnet compound is 200 nm to 2 μm.
[0009] In one embodiment, the negative electrode active material includes a silicon-based material;
[0010] Optionally, based on the mass of the negative electrode active material, the mass percentage of the silicon-based material is 8% to 100%; further optionally, the mass percentage of the silicon-based material is 8% to 50%; further optionally, the mass percentage of the silicon-based material is 10% to 35%;
[0011] Optionally, based on the mass of the negative electrode active material, the negative electrode active material also includes 0% to 92% of a carbon-based material; further optionally, the mass percentage of the carbon-based material is 50% to 92%; further optionally, the mass percentage of the carbon-based material is 65% to 90%.
[0012] In one embodiment, the Dv50 particle size of the silicon-based material is 5 μm to 10 μm; and / or,
[0013] The Dv50 particle size of the carbon-based material is 10 μm to 20 μm.
[0014] In one embodiment, the positive electrode plate includes a positive electrode current collector and a positive electrode active layer located on the surface of the positive electrode current collector, and the positive electrode active layer includes a positive electrode active material; the positive electrode active material includes lithium nickel transition metal oxide;
[0015] Optionally, the chemical formula of the lithium nickel transition metal oxide is LiNi m Co n A (1-m-n)O2, wherein A is selected from one or more of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium and tungsten, 0.5≤m≤1, 0≤n≤0.5, m+n≤1.
[0016] In one of the embodiments, based on the mass of the negative electrode active layer, the mass percentage of the solid electrolyte is 0.2% to 5%.
[0017] In one of the embodiments, based on the mass of the negative electrode active layer, the mass percentage of the negative electrode active material is 90% to 96%.
[0018] In one embodiment, the negative electrode active layer further comprises one or more of the following (a) to (c):
[0019] (a) 0.1% to 9% of a conductive agent, based on the mass percentage in the negative electrode active layer; optionally, the conductive agent comprises one or more of carbon black, graphite, carbon nanotubes, carbon fibers and graphene;
[0020] (b) 0.2% to 5% of a binder, based on the mass percentage in the negative electrode active layer; optionally, the binder comprises one or more of styrene-butadiene rubber, polyacrylic acid (PAA) and polyethylene acrylic acid (PEAA);
[0021] (c) 0.2% to 5% of a thickener, based on the mass percentage in the negative electrode active layer; optionally, the thickener comprises one or both of polyacrylate lithium (PAALi) and carboxymethyl cellulose lithium (CMC-Li).
[0022] In one embodiment, the compaction density of the negative electrode active layer is 1.4 g / cm 3 ~1.8g / cm 3 and / or,
[0023] The double-sided surface density of the negative electrode active layer is 15 mg / cm 2 ~50mg / cm 2 .
[0024] A second aspect of the present application provides an electrical device powered by the secondary battery described in the first aspect.
[0025] The secondary battery mentioned above, by mixing a specific solid electrolyte in the negative electrode, does not need to change the negative electrode main material on a large scale, such as adding hard carbon and other additives, and has little impact on the negative electrode main material, can achieve good ion conductivity, reduce internal resistance, and is particularly suitable for secondary batteries containing silicon negative electrodes, improving their fast charging performance. It also has good discharge performance, high discharge capacity retention rate, and good safety performance.
[0026] At the same time, the above solution is also applicable to traditional graphite negative electrodes and has good universality. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope (SEM) image of the negative electrode sheet prepared in Example 1. DETAILED DESCRIPTION
[0028] The secondary battery and the electric device of the present invention are further described in detail below in conjunction with specific embodiments. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0030] The optional scope of the terms "and / or" and "or / and" used in this article includes any one of two or more related listed items, and also includes any and all combinations of the related listed items, wherein any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items.
[0031] In this article, technical features described in an open manner (such as "including..." or "comprising...") include both closed technical solutions composed of the listed features and open technical solutions containing the listed features.
[0032] Herein, "one or more" refers to any one, any two or more of the listed items. When referring to any two or more of the listed items, it can be a direct mixture of any two or more of the listed items, or it can be any two or more of the listed items connected to each other in a certain connection mode, such as coating, coupling, etc.
[0033] In this document, "first aspect", "second aspect", "third aspect", "fourth aspect", etc. are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0034] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0035] The percentage contents mentioned in this article, unless otherwise specified, refer to mass percentage for solid-liquid mixing and solid-solid mixing, and refer to volume percentage for liquid-liquid mixing.
[0036] The percentage concentrations mentioned in this article, unless otherwise specified, refer to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.
[0037] The temperature parameters involved in this article, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.
[0038] Some examples of the present invention provide a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet;
[0039] The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on the surface of the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material and a solid electrolyte, wherein the solid electrolyte includes a garnet-type compound, and the garnet-type compound includes Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.4 LqCy 1.4 Ta 0.6 O 12 , Li 6.6 LqCy 1.6 Ta 0.4 O 12 , Li 6.75 LqCy 1.75 Ta 0.25 O 12 , Li 6.625 LqCy 1.625 Ta 0.375 O 12 、Li5La3M2O 12 and Li3Zr2Si2PO 12 One or more of; wherein M is selected from one or more of Zr, Ge, Mg and Al.
[0040] Further, the garnet-type compound includes Li7La3Zr2O 12 and / or Li 6.4 La3Zr 1.4 Ta 0.6 O 12 。
[0041] In one example, the Dv50 particle size of the garnet-type compound is 200 nm to 2 μm. By using a garnet-type compound with a suitable particle size, it can be well embedded into the pores of the negative electrode active material, or reasonably adsorbed and distributed on the surface of the negative electrode active material to form an ion channel, thereby further improving the fast charging performance and fast discharging performance of the secondary battery. Specifically, the particle size of the garnet-type compound includes but is not limited to: 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 800 nm, 1 μm, 1.5 μm, 2 μm.
[0042] In one example, the negative electrode active material includes a silicon-based material. The above-described solution of disposing the solid electrolyte in the negative electrode active layer is particularly suitable for silicon-containing negative electrodes and improves the fast charging performance of silicon-containing negative electrodes. Without limitation, the silicon-based material includes one or more of silicon, silicon alloy, silicon oxide compound, and silicon carbide compound. Specifically, examples of the silicon oxide compound include SiOx, nano-SiOx, etc. (0.5 < x < 1.5); examples of the silicon carbide compound include SiCx, etc. (0.5 < x < 1.5). In the present application, SiOx (0.5 < x < 1.5) refers to the average composition general formula of the silicon oxide compound, which may be a mixture as long as the average composition conforms to the above general formula. In the present application, SiCx (0.5 < x < 1.5) refers to the average composition general formula of the silicon carbide compound, which may be a mixture as long as the average composition conforms to the above general formula.
[0043] In one example, based on the mass of the negative electrode active material, the mass percentage of the silicon-based material is 8% to 100%. Specifically, the mass percentage of the silicon-based material includes but is not limited to: 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%. Further, the mass percentage of the silicon-based material is 10% to 35%.
[0044] In one example, based on the mass of the negative electrode active material, the negative electrode active material includes 0% to 92% of carbon-based materials. Specifically, the mass percentage of the carbon-based material includes, but is not limited to: 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 92%. Further, the mass percentage of the carbon-based material is 65% to 90%. Without limitation, the carbon-based material includes one or more of graphite, soft carbon, hard carbon, carbon nanotubes and graphene, and the graphite may specifically be artificial graphite and / or natural graphite.
[0045] In one example, the Dv50 particle size of the silicon-based material is 5 μm to 10 μm. Specifically, the Dv50 particle size of the silicon-based material includes but is not limited to: 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm.
[0046] In one example, the Dv50 particle size of the carbon-based material is 10 μm to 20 μm. Specifically, the Dv50 particle size of the carbon-based material includes but is not limited to: 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm.
[0047] Using a suitable Dv50 particle size of silicon-based materials and / or carbon-based materials can further improve the fast charging performance of the negative electrode plate.
[0048] In one example, based on the mass of the negative electrode active layer, the mass percentage of the solid electrolyte is 0.2% to 5%. Specifically, the mass percentage of the solid electrolyte includes but is not limited to: 0.2%, 0.5%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.5%, 2%, 2.5%, 3%, 4%, 5%. Further, based on the mass of the negative electrode active layer, the mass percentage of the solid electrolyte is 0.5 to 2%.
[0049] In one example, based on the mass of the negative electrode active layer, the mass percentage of the negative electrode active material is 90% to 96%. Specifically, the mass percentage of the negative electrode active material includes but is not limited to: 90%, 91%, 92%, 93%, 94%, 95%, 96%.
[0050] It is understandable that the negative electrode active layer may or may not include additives. Specifically, the additives are selected from one or more of a conductive agent, a binder, and a thickener.
[0051] In one example, the negative electrode active layer further includes 0.01% to 9% of a conductive agent in terms of mass percentage in the negative electrode active layer. Specifically, the mass percentage of the conductive agent includes, but is not limited to, 0.1%, 0.2%, 0.5%, 0.7%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, 7%, and 9%. Without limitation, the conductive agent includes one or more of carbon black, graphite, carbon nanotubes (CNTs), carbon fiber (VGCF), and graphene. Among them, conductive carbon black can be exemplified by acetylene black, Super P, 350G, Ketjen black, etc.; conductive graphite can be exemplified by KS-6, etc.
[0052] In one example, the negative electrode active layer further comprises 0.2% to 5% of a binder by mass percentage in the negative electrode active layer. Specifically, the mass percentage of the binder includes, but is not limited to, 0.2%, 1%, 2%, 2.5%, 3%, 3.5%, 4%, and 5%. Without limitation, the binder includes one or more of styrene-butadiene rubber, polyacrylic acid (PAA), and polyethylene acrylic acid (PEAA).
[0053] In one example, the negative electrode active layer further comprises 0.2% to 5% of a thickener, measured by mass percentage in the negative electrode active layer. Specifically, the mass percentage of the thickener includes, but is not limited to, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 2%, 2.5%, 3%, 4%, and 5%. Without limitation, the thickener comprises one or both of polyacrylate lithium (PAALi) and carboxymethyl cellulose lithium (CMC-Li).
[0054] In one example, the negative electrode active layer does not contain other admixtures, such as soft carbon, hard carbon, etc.
[0055] In one example, the compaction density of the negative electrode active layer is 1.4 g / cm 3 ~1.8g / cm 3 , for example 1.4 g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 .
[0056] In one example, the double-sided surface density of the negative electrode active layer is 15 to 50 mg / cm 2 , for example 15mg / cm 2 、18mg / cm 2 , 20mg / cm 2 , 22mg / cm 2, 25mg / cm 2 、28mg / cm 2 、30mg / cm 2 、32mg / cm 2 、35mg / cm 2 、38mg / cm 2 , 40mg / cm 2 , 42mg / cm 2 , 45mg / cm 2 , 48mg / cm 2 、50mg / cm 2 .
[0057] In one example, the negative electrode current collector is copper foil, carbon-based material, stainless steel, silicon, or a metal with plating / coating.
[0058] In one example, the total thickness of the negative electrode sheet (including the negative electrode current collector and the negative electrode active layer) is 110 μm to 150 μm.
[0059] In addition, in some of the examples, the positive electrode sheet includes a positive current collector and a positive active layer located on the surface of the positive current collector, the positive active layer includes a positive active material; the positive active material includes a nickel-containing positive active material, and further, the positive active material includes a lithium nickel transition metal oxide. The solution of providing a solid electrolyte in the negative electrode active layer as described above is particularly suitable for a battery system containing a silicon negative electrode and a nickel positive electrode, improving its safety performance.
[0060] Without limitation, the chemical formula of the lithium nickel transition metal oxide is LiNi m Co n A (1-m-n) O2, wherein A is selected from one or more of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium and tungsten, 0.5≤m≤1, 0≤n≤0.5, m+n≤1.
[0061] In one example, the chemical formula of the lithium nickel transition metal oxide is LiNi m Co n A (1-m-n) O2, wherein A is selected from one or more of manganese, aluminum, magnesium, zirconium, molybdenum, silver, niobium, and chromium, 0.8≤m≤1, 0≤n≤0.2, and m+n≤1.
[0062] In one example, based on the mass of the positive electrode active layer, the mass percentage of the positive electrode active material is 90% to 96%.
[0063] It is understandable that the positive electrode active layer may or may not include additives. Specifically, the additives are selected from one or more of a conductive agent, a binder and a thickener.
[0064] In one example, the positive electrode active layer further includes 0.01% to 9% of a conductive agent in terms of mass percentage in the positive electrode active layer. Specifically, the mass percentage of the conductive agent includes, but is not limited to, 0.1%, 0.2%, 0.5%, 0.7%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, 7%, and 9%. Without limitation, the conductive agent includes one or more of carbon black, graphite, carbon nanotubes (CNTs), carbon fiber (VGCF), and graphene. Among them, conductive carbon black can be exemplified by acetylene black, Super P, 350G, Ketjen black, etc.; conductive graphite can be exemplified by KS-6, etc.
[0065] In one example, the positive electrode active layer further comprises 0.2% to 5% of a binder by mass percentage in the positive electrode active layer. Specifically, the mass percentage of the binder includes, but is not limited to, 0.2%, 1%, 2%, 2.5%, 3%, 3.5%, 4%, and 5%. Without limitation, the binder includes one or more of polyvinylidene fluoride (PVDF), styrene-butadiene rubber, polyacrylic acid (PAA), and polyethylene acrylic acid (PEAA).
[0066] In one example, the positive electrode active layer further comprises 0.2% to 5% of a thickener, measured by mass percentage in the positive electrode active layer. Specifically, the mass percentage of the thickener includes, but is not limited to, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 2%, 2.5%, 3%, 4%, and 5%. Without limitation, the thickener comprises one or both of polyacrylate lithium (PAALi) and carboxymethyl cellulose lithium (CMC-Li).
[0067] In one example, the positive electrode current collector is Al, Ni, Fe or one of the above metal foils that have been passivated, and can also be one of glassy carbon, graphite foil, graphite sheet, carbon cloth, carbon felt, and carbon fiber.
[0068] It is understandable that there is no particular limitation on the separator, which is used to separate the positive electrode plate from the negative electrode plate. The separator can be made of polyethylene, polypropylene or glass fiber.
[0069] Understandably, the secondary battery further includes an electrolyte. There is no particular limitation on the type of the electrolyte. In one example, the electrolyte contains a lithium salt. Further, the lithium salt includes one or more of LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, and LiN(CF3SO2)2. Even further, the concentration of the lithium salt in the electrolyte is 0.8 M to 1.5 M.
[0070] In one example, the secondary battery is a lithium-ion battery. Without limitation, the lithium-ion battery can be a soft-pack battery, a square shell battery, or a cylindrical battery cell.
[0071] In one example, the battery cell capacity of the secondary battery is 10 Ah to 100 Ah.
[0072] The present invention also provides an electrical device powered by the above secondary battery. Without limitation, examples of the electrical device can include consumer electronics or electric vehicles.
[0073] The following are specific embodiments. Unless otherwise specified, the raw materials used in the embodiments are all commercially available products.
[0074] Example 1
[0075] This example provides a lithium-ion battery, and its manufacturing method is as follows:
[0076] (1) Fabrication of the negative electrode sheet:
[0077] 1.1 Preparation of the negative electrode slurry: Artificial graphite (Dv50 particle size: 15 μm), silicon oxide (molecular formula SiOx, 0.5 < x < 1.5, Dv50 particle size: 8 μm), conductive agent (Super-P), binder (styrene-butadiene rubber), thickener (PAALi), and solid-state electrolyte (garnet-type compound Li 6.4 La3Zr 1.4 Ta 0.6 O 12 powder, Dv50 particle size: 0.4 μm) are proportioned according to a mass percentage of 75.6%:18.9%:0.7%:3%:0.8%:1%. The obtained mixture is added with water according to a solid content of 45%, and stirred evenly to obtain the negative electrode slurry;
[0078] 1.2 The negative electrode slurry in step 1.1 is coated on the negative electrode current collector copper foil, dried in a drying oven at 90 °C, and then roll-pressed and sliced to obtain the negative electrode sheet; the tap density of this negative electrode sheet is 1.6 g / cm 3 , and the double-sided areal density (excluding the foil material) is 40 mg / cm 2 ;
[0079] (2) Fabrication of the positive electrode sheet:
[0080] 2.1 Preparation of positive electrode slurry: LiNi x Co y Mn z O2 (wherein x=0.9, y=0.05, z=0.05), conductive agent (carbon black) and binder (PVDF) are mixed according to the mass percentage of 94%:5%:1%, and N-methyl-2-pyrrolidone (NMP) solvent is added to the obtained mixture according to the solid content of 50%, and stirred evenly to obtain positive electrode slurry;
[0081] 2.2 The positive electrode slurry of step 2.1 was coated on the positive electrode current collector aluminum foil, dried in a drying oven at 110°C, and then rolled and sliced to obtain a positive electrode sheet; the compaction density of the positive electrode sheet was 3.6 g / cm 3 , double-sided surface density is 52mg / cm 2 ;
[0082] (3) Lithium-ion battery assembly:
[0083] The separator (9μm PE base film with 2μm alumina ceramic coated on the upper and lower surfaces), negative electrode sheet, separator and positive electrode sheet are stacked and wound in order and put into an aluminum-plastic bag. After drying, the electrolyte (1 mol / L LiPF6 lithium salt in a DMC / EC / EMC solvent with a mass ratio of 1:1:1) is injected, and finally the lithium-ion battery is obtained after packaging, formation and constant capacity.
[0084] Example 2
[0085] This embodiment provides a lithium ion battery, and its manufacturing method is the same as that of Embodiment 1, except that the weight percentages of artificial graphite, silicon oxide, conductive agent, binder, thickener and solid electrolyte are 65.8%:28.2%:1%:3%:1%:1%.
[0086] Example 3
[0087] This embodiment provides a lithium-ion battery, and its manufacturing method is the same as that of Embodiment 1, with the main difference being that the Dv50 particle size of the solid electrolyte is 200 nm.
[0088] Example 4
[0089] This embodiment provides a lithium-ion battery, and its manufacturing method is the same as that of Embodiment 1, with the main difference being that the Dv50 particle size of the solid electrolyte is 2 μm.
[0090] Example 5
[0091] This embodiment provides a lithium-ion battery, and its manufacturing method is the same as that of Embodiment 1, except that the Super-P conductive agent is replaced by single-walled carbon nanotubes.
[0092] Example 6
[0093] This example provides a lithium-ion battery, and its manufacturing method is the same as that of Example 1. The main difference is that the negative electrode active material uses natural graphite to replace artificial graphite, and the Dv50 particle size of the natural graphite is 10 μm.
[0094] Example 7
[0095] This example provides a lithium-ion battery, and its manufacturing method is the same as that of Example 1. The main difference is that the blended solid electrolyte is replaced with a garnet-type compound Li 6.625 La3Zr 1.625 Ta 0.375 O 12 powder, Dv50 particle size: 0.4 μm.
[0096] Comparative Example 1
[0097] This comparative example provides a lithium-ion battery, and its manufacturing method is the same as that of Example 1. The main difference is that the blended solid electrolyte is replaced with a perovskite-type oxide LLTO (La 0.56 Li 0.33 TiO3 powder, Dv50 particle size: 0.4 μm).
[0098] Comparative Example 2
[0099] This comparative example provides a lithium-ion battery, and its manufacturing method is the same as that of Example 1 in Chinese Patent CN113517419A.
[0100] Comparative Example 3
[0101] This comparative example provides a lithium-ion battery, and its manufacturing method is the same as that of Example 1. The main difference is that no solid electrolyte is added to the slurry of the negative electrode sheet. The specific slurry ratio of the negative electrode sheet is as follows: artificial graphite (Dv50 particle size: 15 μm), silicon oxide (molecular formula SiOx, 0.5 < x < 1.5, Dv50 particle size: 8 μm), conductive agent (Super-P), binder (styrene-butadiene rubber), and thickener (PAALi) are proportioned according to the mass percentage of 76.6%: 18.9%: 0.7%: 3%: 0.8%.
[0102] Test Example:
[0103] Take the lithium-ion batteries (cells) of each example and comparative example, and test them according to the following method:
[0104] (1) DC internal resistance test: After the cell completes the cell standard capacity, use an internal resistance meter to measure the internal resistance value of the cell in the fully charged state. The steps for standard capacity are as follows:
[0105] 1-1) 25±2℃, let stand for 5min;
[0106] 1-2) 25±2℃, charge to 4.25V with 1 / 3C CC-CV, and the cut-off current is 1 / 20C;
[0107] 1-3) 25±2℃, let stand for 30min;
[0108] 1-4) 25±2℃, discharge to 2.5V at 1 / 3C;
[0109] 1-5) 25±2℃, stand for 30min;
[0110] 1-6) Repeat steps 1-2) to 1-5), (the second week calibrated discharge capacity is taken as C0);
[0111] 1-7) 25±2℃, charge to 4.25V with 1 / 3C0 CC-CV, and the cut-off current is 1 / 20C0;
[0112] 1-8) End;
[0113] (2) Ratio test:
[0114] 2-1) 25±2℃, charge to 4.25V with 1 / 2C CC-CV, and the cut-off current is 1 / 20C;
[0115] 2-2) 25±2℃, stand for 30min;
[0116] 2-3) 25±2℃, discharge to 2.5V at 1 / 2C;
[0117] 2-4) 25±2℃, let stand for 30min;
[0118] 2-5) 25±2℃, charge to 4.25V with 1 / 2C CC-CV, and the cut-off current is 1 / 20C;
[0119] 2-6) 25±2℃, stand for 30min;
[0120] 2-7) 25±2℃, discharge at 1C to 2.5V;
[0121] 2-8) 25±2℃, stand for 30min;
[0122] 2-9) 25±2℃, charge to 4.25V with 1 / 2C CC-CV, and the cut-off current is 1 / 20C;
[0123] 2-10) 25±2℃, stand for 30min;
[0124] 2-11) 25±2℃, discharge at 2C to 2.5V;
[0125] 2-12) 25±2℃, stand for 30min;
[0126] 2-13) 25±2℃, charge to 4.25V with 1 / 2C CC-CV, and the cut-off current is 1 / 20C;
[0127] 2-14) 25±2℃, stand for 30min;
[0128] 2-15) 25±2℃, discharge at 3C to 2.5V;
[0129] 2-16)25±2℃, let stand for 30min.
[0130] (3) Step acupuncture:
[0131] The fully charged battery cell was subjected to a step-by-step puncture test. The specific test steps are as follows:
[0132] 3-1) Acupuncture location: center of the large surface of the battery cell;
[0133] 3-2) Needle diameter: 1mm;
[0134] 3-3) Needle tip angle: 30°;
[0135] 3-4) Needle puncture speed: 2 mm / s;
[0136] 3-5) Needle penetration depth: penetrate 1.25mm into the center of the large surface perpendicular to the battery direction, wait for 15s, if there is no loss of control, continue to step 1.25mm until the battery cell is penetrated.
[0137] 4) Surface morphology of the negative electrode sheet: The surface morphology of the negative electrode sheet prepared in Example 1 was observed by scanning electron microscopy (SEM). Figure 1 shown.
[0138] The test results are shown in Table 1 below:
[0139] Table 1
[0140]
[0141] Note: Each battery cell is based on the 1 / 3C discharge capacity. The discharge current of different rates is adjusted to test the discharge capacity of the battery cell and the capacity retention rate is calculated.
[0142] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0143] The above-described embodiments only express several implementation methods of the present invention, which are convenient for understanding the technical solutions of the present invention in detail, but they cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the contents of the attached claims, and the description and drawings can be used to interpret the contents of the claims.
Claims
1. A secondary battery, characterized in that: It includes a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet; The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on the surface of the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material and a solid electrolyte, wherein the solid electrolyte includes a garnet-type compound, and the garnet-type compound includes Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.4 LqCy 1.4 Ta 0.6 O 12 , Li 6.6 LqCy 1.6 Ta 0.4 O 12 , Li 6.75 Ln3Z 1.75 Ta 0.25 O 12 , Li 6.625 LqCy 1.625 Ta 0.375 O 12 、Li5La3M2O 12 and Li3Zr2Si2PO 12 One or more of; wherein M is selected from one or more of Zr, Ge, Mg and Al.
2. The secondary battery according to claim 1, characterized in that: The Dv50 particle size of the garnet compound is 200 nm to 2 μm.
3. The secondary battery according to claim 1, characterized in that: The negative electrode active material comprises a silicon-based material; and / or, The positive electrode plate comprises a positive electrode current collector and a positive electrode active layer located on the surface of the positive electrode current collector, and the positive electrode active layer comprises a positive electrode active material selected from lithium nickel transition metal oxides.
4. The secondary battery according to claim 3, characterized in that: The silicon-based material includes one or more of silicon-oxygen compounds and silicon-carbon compounds; and / or, Based on the mass of the negative electrode active material, the mass percentage of the silicon-based material is 8% to 50%; and / or, Based on the mass of the negative electrode active material, the negative electrode active material includes 50% to 92% of carbon-based material; and / or, The lithium nickel transition metal oxide comprises a metal selected from the formula LiNi m Co n A (1-m-n) One or more compounds of O2, wherein A is selected from one or more of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium and tungsten, 0.5≤m≤1, 0≤n≤0.5, m+n≤1.
5. The secondary battery according to claim 4, characterized in that: Based on the mass of the negative electrode active material, the mass percentage of the silicon-based material is 10% to 35%; and / or, based on the mass of the negative electrode active material, the mass percentage of the carbon-based material is 65% to 90%; and / or, the carbon-based material includes one or more of graphite, soft carbon, hard carbon, carbon nanotubes and graphene; and / or, The Dv50 particle size of the silicon-based material is 5 μm to 10 μm; and / or, The Dv50 particle size of the carbon-based material is 10 μm to 20 μm.
6. The secondary battery according to claim 1, characterized in that: Based on the mass of the negative electrode active layer, the mass percentage of the solid electrolyte is 0.2% to 5%; and / or, based on the mass of the negative electrode active layer, the mass percentage of the negative electrode active material is 90% to 96%.
7. The secondary battery according to claim 6, characterized in that: The negative electrode active layer further comprises one or more of the following (a) to (c): (a) 0.01% to 9% by mass of a conductive agent in the negative electrode active layer; (b) 0.2% to 5% by mass of a binder in the negative electrode active layer; (c) 0.2% to 5% of a thickener, based on the mass percentage in the negative electrode active layer.
8. The secondary battery according to claim 7, characterized in that: The conductive agent includes one or more of carbon black, graphite, carbon nanotubes, carbon fibers and graphene; and / or, The binder comprises one or more of styrene-butadiene rubber, polyacrylic acid and polyethylene acrylic acid; and / or, The thickener includes one or both of lithium polyacrylate and lithium carboxymethyl cellulose.
9. The secondary battery according to any one of claims 1 to 8, characterized in that: The compaction density of the negative electrode active layer is 1.4 g / cm 3 ~1.8g / cm 3 and / or, The double-sided surface density of the negative electrode active layer is 15 mg / cm 2 ~50mg / cm 2 .
10. An electrical device, characterized in that: Power is supplied by the secondary battery according to any one of claims 1 to 9.
Citation Information
Patent Citations
Negative electrode material, negative electrode slurry, battery cell, fast charging battery and preparation method thereof
CN113517419A
